Endocrown in premolar using lithium disilicate-reinforced ceramic: a case report - Nereu Roque Dartora; Michele Bortoluzzi De Conto Ferreira; Aloísio Oro Spazzin; Manoel Damião Sousa Neto; Gustavo Dartora; Erica Alves Gomes (Faculdade Meridional IMED, 2017)
This study reported a clinical case about restoration of an endodontically treated tooth using an endocrown in lithium disilicate-reinforced ceramic fabricated by CAD/CAM system. Case of a female patient, 48 years old who presented coronal fracture of an endodontically treated tooth. Restoration with endocrown in lithium disilicate-reinforced ceramic fabricated by CAD/CAM system was indicated. The crowns were evaluated using a California Dental Association (CDA) quality assessment system at baseline and at follow-up examination. Endocrown in lithium disilicate-reinforced ceramic fabricated by CAD/CAM system was a reliable restorative alternative for an endodontically treated premolar. The minimally invasive prepare for endocrown preserves maximum tooth structure as a gold standard for tooth restorations. In addition, such restorative alternative is advantageous in comparison to conventional full post-and-core supported crown since it presents appropriate mechanical performance and longevity as a lower cost and faster clinical procedure.